Morphine Analgesia Pre-PPCI Is Associated with Prothrombotic State, Reduced Spontaneous Reperfusion and Greater Infarct Size - Farag, Mohamed; Spinthakis, Nikolaos; Srinivasan, Manivannan; Sullivan, Keith; Wellsted, David; Gorog, Diana A. (Thrombosis and Haemostasis, 2018)
The emergency management of ST-elevation myocardial infarction (STEMI) involves treatment with dual-antiplatelet therapy (DAPT) and primary percutaneous coronary intervention (PPCI). Pain is generally treated with opiates, which may delay gastric transit and reduce DAPT absorption. We sought to assess the effect of morphine on reperfusion, infarct size and thrombotic status in 300 patients presenting for PPCI. Morphine was given in a non-randomized fashion as required by emergency teams en route to the heart attack centre. All patients received DAPT and PPCI according to standard care, with optional glycoprotein IIb/IIIa inhibitor (GPI) use. Patients were assessed for ST-segment resolution, coronary flow, thrombotic status and peak troponin. Patients receiving morphine (n = 218; 72.7%) experienced less spontaneous ST-segment resolution pre-PPCI, lower rate of TIMI 2/3 flow in the infarct-related artery pre-PPCI and higher peak troponin level post-PPCI (median [interquartile range]; 1,906 [1,002–4,398] vs. 1,268 [249–2,920] ng/L; p = 0.016) than those who did not. Patients receiving morphine exhibited significantly enhanced platelet reactivity and impaired endogenous fibrinolysis on arrival, compared with no-morphine patients. Morphine administration was an independent predictor of failure of spontaneous ST-segment resolution after adjustment for other variables (odds ratio: 0.26; confidence interval: 0.08–0.84; p = 0.025). Among patients receiving GPI, there was no difference in pre-PPCI flow or peak troponin according to morphine use, suggesting that the adverse effects of morphine relate to delayed DAPT absorption, which may be overcome by GPI. Our hypothesis-generating data suggest that morphine use in STEMI is associated with enhanced platelet reactivity, reduced spontaneous myocardial reperfusion (pre-PPCI) and larger infarct size, and these adverse effects may be influenced by GPI use.Clinical Trial Registration URL: http://www.clinicaltrials.gov. Unique identifier: NCT02562690.
Keywords: opiates; morphine; percutaneous coronary intervention; thrombosis; endogenous fibrinolysis